Litigating for the Environment EU Law, National Courts, and Socio-Legal Reality - Slepcevic, Reinhard; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
The Natura 2000 Directives are the very cornerstone of European Union nature conservation policy which create a considerably stricter environmental protection regime than national laws do. The member states, however, have failed to implement the Directives even despite strong pressure from the European Commission. Reinhard Slepcevic shows how French, German, and Dutch environmental organisations try to enforce the Directives through national courts, though with varied success. The author explains the situation by arguing that it will only be possible to enforce EU law effectively through litigation under particular conditions. The consequences, not only for private judicial law enforcement but also for European integration and democratic governance, are significant. This book is essential reading for researchers and students from the social sciences, in particular sociology and political science, as well as for practitioners in the field of environmental protection.
The Interest in the Judicial Enforcement of EU Law -- Theoretical Approach -- Methodological Approach -- The Natura 2000 Directives -- France -- Germany -- The Netherlands -- Conclusion.
Keywords: Social sciences; Political science; Social Sciences; Political Science; Political Science